Analysis of differentially expressed genes on human X chromosome harboring large deletion induced by X-rays. (6th January 2023) - Hirose, Eri; Yokoya, Akinari; Kawamura, Kasumi; Suzuki, Keiji
Abstract: We examined here normal human cells with large deletions encompassing the hypoxanthine-phosphoribosyltransferase 1 ( HPRT1 ) gene on X chromosome. Expression levels of genes on X chromosome were analyzed by microarray and RT-qPCR method, and differentially expressed genes (DEGs) were extracted. We found that DEGs were not limited to the genes flanking deleted regions but spread over the entire X chromosome. Interestingly, the gene regulation patterns were similar to a large extent among independent clones that have similar-sized large deletions involving the HPRT1 gene. Thus, it is indicated that an impact of large deletion on possible epigenetic transcriptional regulation is not limited to the regions proximal to the deletion region.